Numerical Evaluating Study of the Thermal Initiation Time of Sample Affected by Applied Thermal load (Journal of University of Babylon for Engineering Sciences, 2018)
The thermal initiation time of samples affected by thermal load applied on both faces of the samples was studied numerically using ANSYS-14 during the unsteady heat transfer. Three samples of different lengths (10, 20 and 30) cm were selected, with a constant height of 2.5 cm. Three materials with different thermal properties were selected (high thermal diffusivity (α), medium thermal diffusivity and a low thermal diffusivity) and applied to all three samples. The three samples were subjected to a constant thermal load of 100 °C on one face and the other face to a thermal load of 25 °C. The thermal initiation time of samples was adopted when the temperature of the selected points reached 26 °C, which is 1°C higher than the initial conditions, which can be adopted as a measure of conductivity, and represents the material's response to the heat on it. The aim of this study is to know the thermal initiation time of samples of different lengths, and materials with different thermal properties at a number of points along the samples at the beginning , the middle and the end as a first study .The second study focused on the adoption of a fixed distance(x) from the hot face for all lengths of samples at a number of points with x = (1, 3, 6 and 9)cm. The results of the first study showed that the thermal initiation time of samples  increases with the increase of distance from the hot face and the relationship between them was an exponential positive relationship when fixed the thermal diffusivity. The study also showed that the relationship between the thermal initiation time of samples and the thermal diffusivity was an exponential inverse relationship when the distance from the hot face was fixed. The thermal initiation time of the chromium material with the highest diffusivity at 26 °C ranged from (0.0465 - 207.28) seconds and the low-diffusivity cellular glass material ranged between (3.348 - 21762) seconds to the nearest and farthest point from the hot face. The result of the second study showed that the length of the sample has no effect on the thermal initiation time of sample at the equivalent points located on a fixed distance from the hot face.